A Novel and Robust Approach to Detect Tuberculosis Using Transfer Learning. (25th November 2021) - Faruk, Omar; Ahmed, Eshan; Ahmed, Sakil; Tabassum, Anika; Tazin, Tahia; Bourouis, Sami; Monirujjaman Khan, Mohammad
Abstract : Deep learning has emerged as a promising technique for a variety of elements of infectious disease monitoring and detection, including tuberculosis . We built a deep convolutional neural network (CNN) model to assess the generalizability of the deep learning model using a publicly accessible tuberculosis dataset. This study was able to reliably detect tuberculosis (TB) from chest X-ray images by utilizing image preprocessing, data augmentation, and deep learning classification techniques. Four distinct deep CNNs (Xception, InceptionV3, InceptionResNetV2, and MobileNetV2) were trained, validated, and evaluated for the classification of tuberculosis and nontuberculosis cases using transfer learning from their pretrained starting weights. With an F1-score of 99 percent, InceptionResNetV2 had the highest accuracy. This research is more accurate than earlier published work. Additionally, it outperforms all other models in terms of reliability. The suggested approach, with its state-of-the-art performance, may be helpful for computer-assisted rapid TB detection.